Penyempurnaan indikator keterjangkauan pada sistem peringatan dini kerawanan pangan dan gizi - Yulianis, Nita; Farit Mochamad Afendi,; Suryana, Achmad; Martianto, Drajat; Jannah, Miftahul; Nugraeni, Sri Harjanti; Kusumawardani, Ambar Rukmi Dyah; Imaniyar, Annisa M.; Kurniawan, Arif (Analisis Kebijakan Pertanian, 2025)
The Early Warning System for Food and Nutrition Vulnerability (SKPG) is an important measuring tool for identifying potential food insecurity. However, the current SKPG method shows that the food affordability indicator is less sensitive in capturing changes and does not sharply predict the potential consequences of price changes. This study aims to develop a method for calculating the affordability indicator using price data for six primary food commodities and evaluating alternative scenarios for calculating the price index. The scenarios tested include comparing the current month's price with the average price for the same month in the last one, two, and three years. Evaluation of the correlation of the prices of the six commodities shows that rice and sugar have a strong positive relationship, as do the prices of chicken and cooking oil. The price of eggs has a moderate correlation with these four commodities. The price of corn has a different pattern from the other five commodity prices. These results are used as the basis for constructing a food affordability index using three commodities: rice, chicken eggs, and cooking oil. Calculations based on the new method provide higher sensitivity in detecting potential food insecurity for vulnerable and alert status. It is recommended that this method be adopted to measure the food affordability indicator in the SKPG.